2015
DOI: 10.1002/app.41880
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of flame retardant phase change materials by microencapsulated paraffin and diethyl ethylphosphonate with poly(methacrylic acid‐co‐ethyl methacrylate) shell

Abstract: Microcapsules containing paraffin and diethyl ethylphosphonate (DEEP) flame retardant with uncrosslinked and crosslinked poly (methacrylic acid-co-ethyl methacrylate) (P(MAA-co-EMA)) shell were fabricated by suspension-like polymerization. The surface morphologies of the microencapsulated phase change materials (microPCMs) were studied by scanning electron microscopy. The thermal properties and thermal stabilities of the microPCMs were investigated by differential scanning calorimetry (DSC), and thermal gravim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The fluids containing PCMs are generally classified into two kinds: microencapsulated PCM slurry and PCM emulsion [14]. Although microencapsulated PCM slurries exhibit enhanced specific heat and good fluidity, they suffer from the complex process for preparing PCM microcapsules [15,16], the damage of the capsule walls during transportation by pumps or other machine, and the significant thermal resistance resulted from the thick capsule walls [17]. Comparatively, PCM emulsions have several advantages such as simple process for emulsifying [18], negligible thermal resistance of the protective surfactant layer, and good operation stability [8].…”
Section: Introductionmentioning
confidence: 99%
“…The fluids containing PCMs are generally classified into two kinds: microencapsulated PCM slurry and PCM emulsion [14]. Although microencapsulated PCM slurries exhibit enhanced specific heat and good fluidity, they suffer from the complex process for preparing PCM microcapsules [15,16], the damage of the capsule walls during transportation by pumps or other machine, and the significant thermal resistance resulted from the thick capsule walls [17]. Comparatively, PCM emulsions have several advantages such as simple process for emulsifying [18], negligible thermal resistance of the protective surfactant layer, and good operation stability [8].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies are for FS-PCM and only three ref. [22][23][24] and one patent 25 are on the application of re retardant to mPCMs. There are a few recent studies on microencapsulated PCM that have re retardant encapsulated together with the PCM as given in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the authors suggested that if this rigid PU will be employed in building, the amount of CO 2 leaving to the atmosphere can be reduced resulting in save the energy. Qiu et al prepared the PS foam with microcapsules containing paraffin wax and DEEP as core and PMAA‐co‐EMA as a shell materials and found that micro‐PCM had good thermal regulation potential and TES capacity treated with foam. Later, they synthesised the micro‐PCM of hybrid shell materials of PMMA and UF coated on n ‐tetradecane and found the higher enthalpy of 175.5 J/g.…”
Section: Application Of Micro‐/nano‐pcmsmentioning
confidence: 99%